Agent Checker Mobile Apps for G6PD deficiency children using Rule-Based Technique / Umairah Mohd Zan - Mohd Zan, Umairah (2020)
Glucose 6-Phosphate Dehydrogenase (G6PD) is an enzyme in the body that helps the red blood cells in carrying out oxygen from the lungs to throughout the body. G6PD deficiency can occur when inherited from their parents since the babies are born. This deficiency does not have any medicines to cure it, but they need to avoid certain foods and drugs that may lead to lack of red blood cells in the body which is known as haemolytic anaemia. Unfortunately, people lack of knowledge of G6PD deficiency, especially for types of food and drug to avoid for G6PD deficiency patients. Therefore, system about G6PD deficiency for children is developed in mobile platform that entitled as Agent Checker Mobile Apps for G6PD Deficiency Children using Rule-Based Technique. In addition, this system will be implemented Rule-Based as a technique to accomplish the objectives of the system such as to design a mobile application which check the trigger ingredients of foods and drugs for G6PD deficiency children, to develop a mobile application which check the trigger ingredients of foods and drugs for G6PD deficiency children by using rule-based technique and to test the functionality of the mobile application. Apart from that, Mobile Application Development Life Cycle model (MADLC) is used as the methodology of the system. Last but not least, all the objectives have been matched and supported with the system. Then, this mobile application also will help the parents as the user to be consider more about G6PD deficiency towards their children.